2016
DOI: 10.1589/jpts.28.2625
|View full text |Cite
|
Sign up to set email alerts
|

The effects of performing a one-legged bridge with hip abduction and use of a sling on trunk and lower extremity muscle activation in healthy adults

Abstract: [Purpose] This study investigated the changes in the muscle activities of the trunk and lower limbs of healthy adults during a one-legged bridge exercise using a sling, and with the addition of hip abduction. [Subjects and Methods] Twenty-seven healthy individuals participated in this study (14 males and 13 females). The participants were instructed to perform the bridge exercises under five different conditions. Trunk and lower limb muscle activation of the erector spinae (ES), external oblique (EO), gluteus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…In a study by Choi et al [19], the activity of the internal and EO muscles were greater in the plank posture with hip joint abduction than in the basic plank exercise. Yoon et al [20] reported that the muscle activities of bilateral RA and the IO were greater in the plank posture with hip abduction.…”
Section: Discussionmentioning
confidence: 89%
“…In a study by Choi et al [19], the activity of the internal and EO muscles were greater in the plank posture with hip joint abduction than in the basic plank exercise. Yoon et al [20] reported that the muscle activities of bilateral RA and the IO were greater in the plank posture with hip abduction.…”
Section: Discussionmentioning
confidence: 89%
“…In general, the addition of unstable surfaces while performing lower extremities weight-bearing exercises have been documented to either increase, decrease or cause no change in the muscle activation patterns. [14][15][16]18,[30][31][32][33][34][35] Adding an unstable surface during the performance of the YBT resulted in significantly increased muscle activation in nine (iEOB, iES, cES, GMED, GMAX, BF, VM, RF, VL, MG) out of fifteen muscles in the current study. This is similar to the results found by other authors 18,31 who investigated the effect of various surfaces while performing bridging exercises.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16]18,[30][31][32][33][34][35] Adding an unstable surface during the performance of the YBT resulted in significantly increased muscle activation in nine (iEOB, iES, cES, GMED, GMAX, BF, VM, RF, VL, MG) out of fifteen muscles in the current study. This is similar to the results found by other authors 18,31 who investigated the effect of various surfaces while performing bridging exercises. To overcome the effects of instability, the body tends to attempt to offer stability by increasing the muscle activation of certain muscles.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Choi et al [5] had twenty-seven healthy subjects perform five different bridge conditions to investigate its effects on the erector spinae (ES), external oblique (EO), GM, and biceps femoris (BF). Their findings included significant increases in EO muscle activation during a one-legged bridge with hip abduction and sling compared with the one-legged abduction bridge exercise, significant increases in ipsilateral GM and BF during the one-legged bridge with hip abduction compared with the one-legged bridge exercise, and significant increases in contralateral GM and BF with the one-legged bridge with hip abduction compared with the general bridge exercise.…”
Section: Original Articlementioning
confidence: 99%